Sulfur-Containing Marine Bioactives - Palumbo, Anna (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Sulfur is an essential element for all living organisms and is required by algae, plants, fungi, animals, and humans for growth and development. It is present in a variety of biomolecules involved in many biological functions, including the maintenance of cell redox homeostasis, defense, and detoxifying processes. The alteration of sulfur compound metabolism may lead to human diseases as well as to plant and animal pathologies. The marine environment, which is characterized by a high biodiversity of species and a great chemical diversity, represents a great potential source of bioactive sulfur molecules. A broad range of biologically active sulfur compounds with unique structures and pharmacological properties have been reported to occur in marine organisms, from amino acids to different sulfated derivatives. Great attention is also focused on sulfur metabolites in the marine microbial world in relation to the global sulfur cycle. The aim of this Special Issue is to present existing knowledge and recent studies on sulfur-containing marine bioactive compounds in different biological systems. Attention is also focused on metabolites active at the ecological level.